Financial Stability of Islamic versus Conventional Banks in Pakistan - Abrar, Tanveer; Ahmed, Farhan; Kashif, Muhammad (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
This study aims to analyze and compare the financial stability of Pakistani banks covering a timeframe of 5 years from 2012 to 2016. This study employs the financial soundness indicators of the International Monetary Funds and State Bank of Pakistan and the z-score index. The comparative analysis through average scores is performed using 3 indicators of financial stability namely Z-Score, Capital Adequacy Ratio (CAR) and Equity to Total Assets Ratio. The findings of the research reveal that (i) conventional banks are more financially stable than Islamic banks; (ii) large conventional banks are more financially stable than large Islamic banks; (iii) small Islamic banks are less stable than small conventional bank. The implication of this paper is that conventional banks have the potential of absorbing financial stability shock as compare to Islamic banks on the basis of stated financial soundness indicators and Z-Score specifically.DOI: 10.15408/aiq.v10i2.6500